HCI 2020: Looking Back to the Future - Sellen, Abigail (CHI Conference on Human Factors in Computing Systems, 2021)
In March, 2007, a forum entitled HCI 2020: Human Values in a Digital Age, was held in Sanlúcar la Mayor, Spain, just outside Seville. Its purpose was to gather luminaries in computing, design, social sciences, and scientific philosophy to discuss, debate and help formulate an agenda for human-computer interaction (HCI) over the next decade and beyond. This resulted in a detailed report, released in April 2008, in the form of a book called Being Human: Human-Computer Interaction in the Year 20201, authored by 45 members of the wider HCI community. In this panel, we shall build from four core questions. How successfully did the HCI 2020 forum and report recognize trends and shape HCI? What major trends or issues did they fail to anticipate? How valuable to the HCI community, to the participants, and to the sponsoring organizations was the forum and the report? And finally, what does this history suggest about both the process and the ultimate value to HCI, to computing in general, and to the world, of creating a HCI 2035 vison?.